Crítica da BNCC: implicações da sua implementação na educação infantil na visão de gestores e docentes da Rede Pública Municipal de Ensino de Mococa - São Paulo - Coelho, Natália Colpani Albertino (2024)
This master’s research was developed within the State line, Policies and Management in Education of the Graduate Program in Education (PPGED) of the Federal University of Uberlândia (UFU). It is a qualitative, descriptive and critical study of the National Common Core Curriculum (BNCC), as well as its implementation policy and its implications in the concrete reality of Early Childhood Education in the public school system of the city of Mococa, located in the northeast region of the interior of the state of São Paulo. As a result, both of an analysis of the FC - 1988, the RCNEI - 1988, the LDBN - Law 9394/96, the PNE - Federal Law No. 13.005 of 06/25/2014, the DCN for Early Childhood Education - 2009 and the BNCC (final version) dated 12/20/2017, as well as a bibliographic review, it was possible to identify and describe public policies for the educational care of children from 0 to 3 years old, with an emphasis on studying their ideological implications in concrete reality, in the period between 1988 and 2017. In addition, a critical analysis of the BNCC for Early Childhood Education was carried out and a study was presented regarding its implementation in the Municipal Public Education Network of Mococa-SP, based on documentary analysis and the contents resulting from the application of an online questionnaire sent and answered by 20 professionals in the area of Early Childhood Education (managers and teachers), starting in 2017. The research has shown that public policies aimed at children aged 0 to 3 have moved, in modernity, from the field of welfare policies to the field of educational policies. In this context, a set of contradictions was identified between the discourse prescribed in the law and the concrete reality. These contradictions can be seen in the fact that Early Childhood Education is now faced with the challenge of becoming an actual educational policy indeed, however, in concrete reality, we are faced with welfare and philanthropic visions and practices that reproduce the traditional logic of a school which, in addition to disregarding the child as a person in his or her singularity, treats them as subjects who attend school basically to meet the needs of the world of work of their respective responsible family members. In an attempt to overcome this traditional school model, it was realized in the public school system in Mococa-SP that, it was only in 2000, the schools of early childhood education for children aged 0 to 3, began to make the transition from social assistance to formal education. However, this transition took place without the adoption of public policies with effective economic support and continuing training processes for teachers capable of transforming schools from both a political and pedagogical point of view, thus not guaranteeing the necessary appreciation and respect sought by educators in this school network. In this context, the process of implementing the BNCC from 2017 took place in a verticalized way and without the proper preparation of education professionals to understand its foundations and methodological procedures for its implementation in the school reality. Finally, the research also showed that while continuing training in service does not become a permanent process, democratic, face-to-face, dialogical, participatory and critical process, which guarantees the construction of knowledge by those who actually think about and put the curriculum into practice, there will be no curriculum proposal, such as the BNCC, that can be put into practice to meet the true emancipatory aspirations of the people who have been fighting, with a lot of effort and dedication, for critical and transformative education in this country.